Storing carbon dioxide for climate's sake: contradictions and parallels with enhanced oil recovery - Rodriguez, Emily (Frontiers in Climate, 2023)
An increase in carbon capture and storage (CCS) projects, including bioenergy with CCS (BECCS), has led to an urgent demand for storage sites, and Norway stands out for its ongoing and planned geological storage sites in a European context. Even though there are no commercial carbon dioxide enhanced oil recovery (CO2-EOR) projects in Norway and the North Sea, there is scientific literature linking CO2-EOR and CCS in this geographical region. CO2-EOR utilizes CO2 to extract additional oil, counteracting the climate change mitigation purpose of geological storage. This review article explores how CCS is represented in the scientific literature on CO2-EOR in the North Sea and Norway, with a focus on system synergies and contradictions in relation to climate change mitigation. The main themes in the scientific literature on CO2-EOR in the North Sea are climate change, economics, and geological feasibility. Monitoring, safety, and leakage in addition to transportation of CO2 are less salient. The results show that there are contrasting framings in the literature. One framing is that CO2-EOR is a gateway to large-scale storage which maintains, or even expands, the extraction of fossil fuels and contributes to a sustainable transition in the long run through knowledge building and shared infrastructure. In contrast, another framing is that CO2-EOR combined with CCS have goal conflicts and are therefore not compatible, illustrating complexities with geological storage. Finally, this study reflects on how techno-economic research on CO2 storage in the North Sea and Norway is furthered through critical social science perspectives.